Interaction of 2-(2′, 4′-bromophenoxyl)-benzoquinone with deoxynucleosides and DNA in vitro. (January 2015) - Huang, Lihua; Li, Charlie; Lai, Yongquan; Qiu, Bin; Cai, Zongwei
Highlights: 2′4′BrPhO-BQ could covalently bind to DNA mediated by quinone group. The PBDE quinone metabolite formed various DNA adducts with dG, dA and dC via Michael Addition. The adducts were detected from reaction of the quinone with Calf Thymus DNA. The adducts were confirmed by electrospray ionization-tandem mass spectrometry. Abstract: Polybrominated diphenyl ethers (PBDEs) may be metabolized to form hydroxylated and quinone products. Study on the formation of DNA adducts altered by PBDEs quinones was conducted. Various types of DNA adducts generated from in vitro reaction of deoxyguanosine (dG), 2′-deoxyadenosine (dA), 2′-deoxycytidine (dC), thymidine (T) and DNA with a PBDE–quinone metabolite, namely 2-(2′, 4′-bromophenoxyl)-benzoquinone (2′4′BrPhO-BQ) were characterized. The results suggest that the quinone compound could form various DNA adducts with dG, dA and dC via Michael Addition, which was confirmed from analyses by electrospray ionization tandem mass spectrometry. Two adducts were respectively generated from the reactions of 2′4′BrPhO-BQ with dC and dG, while three adducts were produced with dA. The formation of adducts of 2′4′BrPhO-BQ-deoxynucleoside changed with different pH of reaction solution. The obtained results demonstrated that 2′4′BrPhO-BQ could covalently bind to DNA mediated by quinone group. The in vitro data of the formation of DNA adducts might be valuable to elucidate the mechanism of interaction between PBDEs and DNA in vivo .